2003
DOI: 10.1016/s0890-6955(03)00184-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic chatter detection in grinding

Abstract: Two methods for automatic chatter detection in outer diameter plunge feed grinding are proposed. The methods employ entropy and coarse-grained information rate (CIR) as indicators of chatter. Entropy is calculated from a power spectrum, while CIR is calculated directly from fluctuations of a recorded signal. The methods are verified using signals of the normal grinding force and RMS acoustic emission. The results show that entropy and CIR perform equally well as chatter indicators. Based on the normal grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 11 publications
(20 reference statements)
0
27
0
4
Order By: Relevance
“…This undesirable phenomenon has been a popular area of machining research, with numerous developments on its detection and control. Although it has been found that "normal force is more sensitive to chatter vibration than AE" techniques [40], it has also been reported that tool chatter indirectly influences the AE sources, causing some changes to the signal [7]. This is of particular interest when the AE spike phenomenon is considered, as many of the features associated with grinding can be related, as shown in …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This undesirable phenomenon has been a popular area of machining research, with numerous developments on its detection and control. Although it has been found that "normal force is more sensitive to chatter vibration than AE" techniques [40], it has also been reported that tool chatter indirectly influences the AE sources, causing some changes to the signal [7]. This is of particular interest when the AE spike phenomenon is considered, as many of the features associated with grinding can be related, as shown in …”
mentioning
confidence: 99%
“…Due to its much lower frequency response, it has been found to be far more sensitive to chatter vibration than AE [40]. With chatter frequencies in grinding generally found to lie well under 1000 Hz [43,39], it is fair to assume that the AE technique is not best suited for detecting this type of phenomenon.…”
mentioning
confidence: 99%
“…Najczęściej używane do tego celu sygnały to siła skrawania, moc wrzeciona ściernicy, emisja akustyczna [4] bądź też drgania [5,6,7]. W większości przypadków każda z tych metod wymaga umieszczenia czujnika w pobliżu strefy obróbki.…”
Section: Wprowadzenieunclassified
“…Poważnym problemem wystepującym podczas realizacji tego procesu jest również problem właściwego doprowadzenia chłodziwa, szczególnie fazie rozpoczynania szlifowania gdy część strugi chłodziwa rozpraszana jest podczas zderzenia z powierzchnią boczną przedmiotu obrabianego. Może to powodować powstawanie przypaleń szlifierskich [9].…”
Section: Wprowadzenieunclassified